Brain-derived neurotrophic factor, depressive symptoms and somatic comorbidity in patients with coronary heart disease. Issue 1 (24th February 2021) - Tschorn, Mira; Kuhlmann, Stella Linnea; Rieckmann, Nina; Beer, Katja; Grosse, Laura; Arolt, Volker; Waltenberger, Johannes; Haverkamp, Wilhelm; Müller-Nordhorn, Jacqueline; Hellweg, Rainer; Ströhle, Andreas
Abstract: Objective: Depression and coronary heart disease (CHD) are highly comorbid conditions. Brain-derived neurotrophic factor (BDNF) plays an important role in cardiovascular processes. Depressed patients typically show decreased BDNF concentrations. We analysed the relationship between BDNF and depression in a sample of patients with CHD and additionally distinguished between cognitive-affective and somatic depression symptoms. We also investigated whether BDNF was associated with somatic comorbidity burden, acute coronary syndrome (ACS) or congestive heart failure (CHF). Methods: The following variables were assessed for 225 hospitalised patients with CHD: BDNF concentrations, depression [Patient Health Questionnaire-9 (PHQ-9)], somatic comorbidity (Charlson Comorbidity Index), CHF, ACS, platelet count, smoking status and antidepressant treatment. Results: Regression models revealed that BDNF was not associated with severity of depression. Although depressed patients (PHQ-9 score >7) had significantly lower BDNF concentrations compared to non-depressed patients ( p = 0.04), this was not statistically significant after controlling for confounders ( p = 0.15). Cognitive-affective symptoms and somatic comorbidity burden each closely missed a statistically significant association with BDNF concentrations ( p = 0.08, p = 0.06, respectively). BDNF was reduced in patients with CHF ( p = 0.02). There was no covariate-adjusted, significant association between BDNF and ACS. Conclusion: Serum BDNF concentrations are associated with cardiovascular dysfunction. Somatic comorbidities should be considered when investigating the relationship between depression and BDNF.